Modified Lemaire tenodesis reduces anterior cruciate ligament graft forces during internal tibial torque loading - Raul Mayr; Maximilian Sigloch; Christian Coppola; Romed Hoermann; Alessandra Iltchev; Werner Schmoelz (Journal of Experimental Orthopaedics)
Abstract Purpose The aim of the study was to directly measure graft forces of an anterior cruciate ligament reconstruction (ACLR) and a lateral extra‐articular tenodesis (LET) using the modified Lemaire technique in combined anterior cruciate ligament (ACL) deficient and anterolateral rotatory instable knees and to analyse the changes in knee joint motion resulting from combined ACLR + LET. Methods On a knee joint test bench, six fresh‐frozen cadaveric specimens were tested at 0°, 30°, 60°, and 90° of knee flexion in the following states: 1) intact; 2) with resected ACL; 3) with resected ACL combined with anterolateral rotatory instability; 4) with an isolated ACLR; and 5) with combined ACLR + LET. The specimens were examined under various external loads: 1) unloaded; 2) with an anterior tibial translation force (ATF) of 98 N; 3) with an internal tibial torque (IT) of 5 Nm; and 4) with a combined internal tibial torque of 5 Nm and an anterior tibial translation force of 98 N (IT + ATF). The graft forces of the ACLR and LET were recorded by load cells incorporated into custom devices, which were screwed into the femoral tunnels. Motion of the knee joint was analysed using a 3D camera system. Results During IT and IT + ATF, the addition of a LET reduced the ACLR graft forces up to 61% between 0° and 60° of flexion (P = 0.028). During IT + ATF, the LET graft forces reached 112 N. ACLR alone did not restore native internal tibial rotation after combined ACL deficiency and anterolateral rotatory instability. Combined ACLR + LET was able to restore native internal tibial rotation values for 0°, 60° and 90° of knee flexion with decreased internal tibial rotation at 30° of flexion. Conclusion The study demonstrates that the addition of a LET decreases the forces seen by the ACLR graft and reduces residual rotational laxity after isolated ACLR during internal tibial torque loading. Due to load sharing, a LET could support the ACLR graft and perhaps be the reason for reduced repeat rupture rates seen in clinical studies. Care must be taken not to limit the internal tibial rotation when performing a LET.